Ethics and the New Conditions for Coverage for End-Stage Renal Disease Facilities - Schrag, LMSW, ACSW, Wendy Funk (The Journal of Nephrology Social Work, 2008)
Social workers bring a unique perspective of values and ethical decision-making skills to their work environments. Trained in the basic values of service, social justice, dignity and worth of individuals, importance of human relationships, integrity and competence, social workers are equipped to help the health care team face ethical dilemmas and use these values to promote ethical decision making. The new Conditions for Coverage for End-Stage Renal Disease Facilities include some new guidance on current ethical dilemmas. These include the patient care environment, patient rights, advance care planning and involuntary discharge. At this critical juncture, social workers can assist their health care team in creating new processes and policies for ethically-sound practice with people on dialysis.